2023
DOI: 10.3390/life13041019
|View full text |Cite
|
Sign up to set email alerts
|

Acai Berry (Euterpe sp.) Extracts Are Neuroprotective against L-Glutamate-Induced Toxicity by Limiting Mitochondrial Dysfunction and Cellular Redox Stress

Abstract: Aberrant accumulation of the neurotransmitter L-glutamate (L-Glu) has been implicated as a mechanism of neurodegeneration, and the release of L-Glu after stroke onset leads to a toxicity cascade that results in neuronal death. The acai berry (Euterpe oleracea) is a potential dietary nutraceutical. The aim of this research was to investigate the neuroprotective effects of acai berry aqueous and ethanolic extracts to reduce the neurotoxicity to neuronal cells triggered by L-Glu application. L-Glu and acai berry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…ATP levels are also used as a surrogate for cell viability since lethal cell damage and a loss of membrane integrity results in an inability to synthesize ATP and a corresponding reduction in cellular ATP levels [ 43 , 44 ]. A decline in ATP levels can match the IC 50 values generated by MTT and/or LDH assays in undifferentiated and differentiated SH-SY5Y cells in response to different neurotoxicants [ 27 , 32 ]. However, in our study, the sensitivity to MQ indicated notable potency for limiting mitochondrial function and blunting the generation of intracellular ATP ( Figure 4 ), with a 24-h IC 50 value of approximately 6 µM, lower than that estimated by MTT or LDH assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ATP levels are also used as a surrogate for cell viability since lethal cell damage and a loss of membrane integrity results in an inability to synthesize ATP and a corresponding reduction in cellular ATP levels [ 43 , 44 ]. A decline in ATP levels can match the IC 50 values generated by MTT and/or LDH assays in undifferentiated and differentiated SH-SY5Y cells in response to different neurotoxicants [ 27 , 32 ]. However, in our study, the sensitivity to MQ indicated notable potency for limiting mitochondrial function and blunting the generation of intracellular ATP ( Figure 4 ), with a 24-h IC 50 value of approximately 6 µM, lower than that estimated by MTT or LDH assays.…”
Section: Discussionmentioning
confidence: 99%
“…The final product was measured spectrophotometrically at 490 nm and 680 nm using a Varioskan™ LUX multimode microplate reader (ThermoFisher Scientific, Waltham, MA, USA). The reading taken at 680 nm absorbance value was subtracted from the 490 nm absorbance value to calculate LDH activity as previously described [ 27 ]. The OD values for each of the treatments were normalised to the mean of the negative control, and the percentage of LDH production was determined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, PQ accumulates in mitochondria and acts as a potent redox cycler that converts free radicals interacting with molecular oxygen to form superoxide and other ROS [12,13]. In addition, PQ can elevate ROS generation through glutamate excitotoxicity by Ca 2+ efflux, depolarization of N-methyl-D-aspartate (NMDA) receptor channels, and activation of non-NMDA receptor channels, although activation of NMDA receptors may be limited in SH-SY5Y cells [56]. Therefore, our research study outcomes are consistent with previous studies suggesting that PQ can induce oxidative stress through mechanisms that in part involve ROS generation and inhibition of mitochondrial complex I, but this may be augmented by additional mechanisms that were not studied further.…”
Section: Discussionmentioning
confidence: 99%